Physics Class Is an Extension of the Math Class: Perceptions of High School Students on the Teachings of Physics [la Clase de Física Es Una Extensión de la Clase de Matemática: Percepciones de Estudiantes de Enseñanza Media Sobre la Enseñanza de la Física] - Vanegas-Ortega, C (Universidad Austral de Chile, 2021)
The aim of this research is to characterize the perceptions that high school students from the Santiago Metropolitan Region of Chile have about mathematics in physics classes. The study was carried out with 1222 high school students, a 36-question Likert scale questionnaire was applied to them, distributed in four dimensions: natural sciences, mathematics, physics, and physics class. The results show that although the study participants perceive tangential differences between the physics and mathematics classes, they consider the physics class to be an additional class of mathematics (applied mathematics). These results put stress on practicing physics teachers and the training of physics teachers because it demands research on the best ways for classes to go through the processes of modeling, formalization and mathematization, so that students can develop closer views. to the nature of physics © 2021. Estudios Pedagogicos.All Rights Reserved